Cinnamon essential oil causes cell membrane rupture and oxidative damage of Rhizopus stolonifer to control soft rot of peaches - Zhao, Zichang; Yu, Mingxia; Wei, Yingying; Xu, Feng; Jiang, Shu; Chen, Yi; Ding, Phebe; Shao, Xingfeng (Elsevier Ltd, 2025)
Rhizopus stolonifer is the major cause of soft rot in peaches, which leads to rapid decay and shortens the shelf life. In this study, we investigated the inhibitory mechanism of cinnamon essential oil (CEO) against R. stolonifer, evaluated its control efficacy of soft rot of peaches. The results showed that CEO treatment damaged the cell membrane of R. stolonifer, resulting in a high increase in extracellular conductivity and protein content. CEO causes the mycelium to crumple, as well as plasmalemma wall separation, the ablation and absence of some organelles. CEO also increased the contents of malondialdehyde (MDA) and hydrogen peroxide (H2O2), and the accumulation of reactive oxygen species (ROS) of R. stolonifer, thus inhibiting the growth of R. stolonifer. In addition, we found that 0.8 mL L−1 CEO fumigation significantly reduced the incidence of soft rot in peaches without any adverse effect on fruit quality. Therefore, our findings provide theory and scientific guide for the application of CEO in controlling soft rot of peaches in postharvest storage. CEO could be used as a natural fungicide to reduce fungal decay in fruits.